2000
DOI: 10.1006/aphy.2000.6048
|View full text |Cite
|
Sign up to set email alerts
|

Charges from Dressed Matter: Construction

Abstract: There is a widespread belief in particle physics that there is no relativistic description of a charged particle. This is claimed to be due to persistent, long range interactions which distort the in and out going plane waves and generate infra-red divergences. In this paper we will show that this is not the case in QED. We construct locally gauge invariant charged fields which do create in and out Fock states. In a companion paper we demonstrate that the Green's functions of these fields have a good pole stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
151
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(153 citation statements)
references
References 52 publications
1
151
0
1
Order By: Relevance
“…The boson clouds of the Faddeev-Kulish states have been shown, in [9] for QED and [10] for gravity, to precisely cancel the vacuum transitions induced by the scattering operator, which explains why Faddeev-Kulish states yield well-defined S-matrix elements. Also, it has been shown in [11] that a gauge-invariant formulation of the charged particles in QED analogous to [12,13] JHEP02(2018)171 yields coherent states that are essentially equivalent to Faddeev-Kulish states, which turn out to be the charge eigenstates of the large gauge symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…The boson clouds of the Faddeev-Kulish states have been shown, in [9] for QED and [10] for gravity, to precisely cancel the vacuum transitions induced by the scattering operator, which explains why Faddeev-Kulish states yield well-defined S-matrix elements. Also, it has been shown in [11] that a gauge-invariant formulation of the charged particles in QED analogous to [12,13] JHEP02(2018)171 yields coherent states that are essentially equivalent to Faddeev-Kulish states, which turn out to be the charge eigenstates of the large gauge symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…This has been taken [1] to mean that one cannot describe charged particles in gauge theories. In a series of papers [2][3][4][5][6] we have shown that this conclusion is overly hasty: it is in fact possible to construct gauge invariant operators whose S-matrix elements are free of infra-red divergences. These fields have been shown to asymptotically recover a particle description of charges and to have a rich structure which is physically reflected in the cancellation of both soft and phase divergences.…”
Section: Introductionmentioning
confidence: 99%
“…We further presented an equation with which we could generate these dressed fields corresponding to physical charges. For the purposes of this paper, we may summarise the results of I in one equation: we claim 4 that the locally gauge invariant field…”
Section: Introductionmentioning
confidence: 99%